Identifying recommendation domains for targeting dual-purpose maize-based interventions in crop-livestock systems in East Africa - Notenbaert, An Maria Omer; Herrero, Mario; You, Liangzhi; González Estrada, E.; Quirós, Carlos F.; Blümmel, Michael (International Livestock Research Institute, 2008)
Livestock are recognized as essential assets for the livelihoods of poor farmers in the mixed crop-livestock systems throughout the tropics, while feed resources have been identified as an important constraint to their productivity. Two international agricultural research institutes, CIMMYT and ILRI, therefore joined forces in a project designed to improve the value of maize as livestock feed with an aim of enhancing the livelihoods of maize-livestock farmers in East-Africa. The first issue addressed in the initiative and the topic of this paper was deciding where to work so as to maximize the chances of successful testing of the new varieties and at the same time grasp a better understanding of the context-specific incentives for adoption of these varieties. Several lessons were learnt from the process, including the increased utility of targeting when the bio-physical and socio-economic are freely combined, and the continued need for baseline spatial data to improve the targeting of research in the future that is designed to improve the livelihoods of poor livestock keepers in East-Africa.